Latex composition, molded article, and method for producing molded article

The use of a thiol compound with multiple mercapto groups in the chloroprene polymer latex composition addresses the environmental concerns of traditional crosslinking accelerators, achieving equivalent or better performance in molded articles like surgical gloves.

JP7619282B2Active Publication Date: 2025-01-22RESONAC CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021570045
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-06
Filing Date
2021-01-05
Publication Date
2025-01-22
Estimated Expiration
2041-01-05

AI Technical Summary

Technical Problem

Existing chloroprene polymer latex crosslinking processes rely on crosslinking accelerators like 1,3-diphenyl-2-thiourea, which have a high environmental impact, necessitating the use of substances with lower environmental impact for crosslinking.

Method used

A latex composition containing a chloroprene polymer and a thiol compound with two or more mercapto groups in one molecule, such as 1,4-bis(3-mercaptobutyryloxy)butane, is used for crosslinking, replacing traditional high-impact accelerators.

Benefits of technology

This approach allows for crosslinking with a lower environmental impact while maintaining or improving the performance of the molded articles, such as surgical gloves, by forming a crosslinked structure that enhances elasticity and reduces breaking strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619282000001
    Figure 0007619282000001
  • Figure 0007619282000002
    Figure 0007619282000002
Patent Text Reader

Abstract

The present invention relates to a latex composition, a molded body and a method for producing a molded body; and the latex composition contains (A) a chloroprene polymer and (B) a thiol compound that has two or more mercapto groups in each molecule.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a latex composition, a molded article, and a method for producing a molded article. [Background technology]

[0002] Chloroprene polymer latex has good general rubber properties, weather resistance, heat resistance, chemical resistance, etc., and is used in various applications. Chloroprene polymer latex is widely used in, for example, dipped products such as gloves, adhesives, and civil engineering and construction applications such as elastic asphalt (modified asphalt) and elastic cement. In particular, when disposable medical gloves such as surgical gloves are manufactured using chloroprene polymer latex, they often fit the user's hand as well as gloves made of natural rubber, giving the user a good fit (comfort), and allowing them to respond to fine movements of the user's fingertips.

[0003] As a related technique, a chloroprene copolymer latex for producing a flexible molded article has been proposed (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-143002 A Summary of the Invention [Problem to be solved by the invention]

[0005] In order to manufacture a molded article from a chloroprene polymer latex, a crosslinking treatment is performed, and a crosslinking accelerator is often used in the crosslinking treatment. Furthermore, 1,3-diphenyl-2-thiourea, ethylenethiourea, and the like are often used as crosslinking accelerators. However, it is desirable to use substances with a smaller environmental impact in the crosslinking treatment of the chloroprene polymer.

[0006] An object of the present invention is to provide a latex composition which enables crosslinking of a chloroprene polymer using substances which have a relatively small environmental impact. [Means for solving the problem]

[0007] The present inventors have conducted extensive research to solve the above problems, and have found that the above problems can be solved by adding a thiol compound (B) having two or more mercapto groups in one molecule to a latex composition instead of a crosslinking accelerator that has a high environmental impact, and have completed the present invention. That is, the present invention relates to, for example, the following items [1] to

[12] .

[0008] [1] A latex composition comprising a chloroprene polymer (A) and a thiol compound (B) having two or more mercapto groups in one molecule.

[0009] [2] The latex composition according to [1], wherein the chloroprene polymer (A) is at least one selected from the group consisting of a homopolymer of chloroprene and a copolymer of chloroprene and another monomer copolymerizable with the chloroprene.

[0010] [3] The latex composition according to [2], wherein the ratio of the other monomer in the monomers used to form the chloroprene polymer (A) is 30 mass% or less.

[0011] [4] The latex composition according to any one of [1] to [3], wherein the thiol compound (B) has a primary mercapto group or a secondary mercapto group.

[0012] [5] The latex composition according to any one of [1] to [4], wherein the thiol compound (B) has 2 to 10 mercapto groups in one molecule.

[0013] [6] The latex composition according to any one of [1] to [5], wherein the thiol compound (B) has two or more partial structures represented by CH3(SH)CHCH2COOCH2- in one molecule.

[0014] [7] The latex composition according to any one of [1] to [6], wherein the thiol compound (B) is at least one selected from the group consisting of 1,4-bis(3-mercaptobutyryloxy)butane, 1,3,5-tris(2-(3-sulfanylbutanoyloxy)ethyl)-1,3,5-triazinane-2,4,6-trione, pentaerythritol tetrakis(3-mercaptobutyrate), and trimethylolpropane tris(3-mercaptobutyrate).

[0015] [8] The latex composition according to any one of [1] to [7], further comprising a metal oxide. [9] The latex composition according to [8], wherein the metal oxide is zinc oxide.

[0016]

[10] The latex composition according to any one of [1] to [9], wherein the content of the thiol compound (B) is 0.05 to 20 parts by mass when the content of the chloroprene polymer (A) is 100 parts by mass.

[0017]

[11] A molded article formed using the latex composition according to any one of [1] to

[10] .

[0018]

[12] A method for producing a molded article, comprising heating the latex composition according to any one of [1] to

[10] . Effect of the Invention

[0019] According to the present invention, it is possible to provide a latex composition which enables crosslinking of a chloroprene polymer using a substance which has a relatively small environmental impact. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited to the configurations of the following embodiments. Each of the components described below can be used alone or in combination.

[0021] [Latex composition] One embodiment of the latex composition according to the present invention (hereinafter also referred to as "the composition of the present embodiment") contains a chloroprene polymer (A) and a thiol compound (B) having two or more mercapto groups in one molecule (hereinafter also simply referred to as "thiol compound (B)"). The latex composition can be prepared by any preparation method capable of dispersing fine particles of the chloroprene polymer (A) and the thiol compound (B) in a dispersion medium such as water. For example, the latex composition can be prepared from fine particles of the chloroprene polymer (A) and the thiol compound (B), or can be prepared by mixing a chloroprene polymer latex and a thiol compound (B). Here, the chloroprene polymer latex is a latex in which fine particles of the chloroprene polymer (A) are dispersed in a dispersion medium such as water.

[0022] The latex composition may contain components other than the chloroprene polymer (A) and the thiol compound (B). For example, the latex composition may contain additives such as an emulsifier, a chain transfer agent, and a stabilizer, within the scope of the present invention.

[0023] <Chloroprene polymer (A)> The chloroprene polymer (A) may be a homopolymer of 2-chloro-1,3-butadiene (chloroprene) monomer, or may be a copolymer of chloroprene and other monomers copolymerizable with chloroprene (hereinafter also referred to as "chloroprene copolymer"). The chloroprene homopolymer does not have structural units derived from monomers other than chloroprene. On the other hand, the chloroprene copolymer has structural units derived from the chloroprene monomer and structural units derived from a comonomer. Here, the comonomer is another monomer copolymerizable with chloroprene.

[0024] Examples of the comonomer include butadiene, butadiene derivatives other than chloroprene, styrene, acrylonitrile, acrylic acid, acrylic acid derivatives, methacrylic acid, and methacrylic acid derivatives. Examples of the butadiene derivatives include alkylated 1,3-butadiene and chlorinated 1,3-butadiene. Examples of the alkylated 1,3-butadiene include isoprene. Examples of the chlorinated 1,3-butadiene include 2,3-dichloro-1,3-butadiene and 1-chloro-1,3-butadiene. Examples of the acrylic acid derivatives include esters of acrylic acid. Examples of the methacrylic acid derivatives include esters of methacrylic acid. The proportion of the comonomer in the monomers used to form the chloroprene polymer (A) is preferably 30 mass% or less, more preferably 5 mass% or less, and even more preferably 0 mass%. When the proportion of the comonomer is 30 mass% or less of the monomers used to form the chloroprene polymer (A), the crosslinking treatment can be carried out well.

[0025] When the chloroprene polymer (A) is a chloroprene homopolymer, the crosslinking rate is faster than when the chloroprene polymer (A) is a chloroprene copolymer, and therefore, in order to shorten the crosslinking time, it is preferable to use a chloroprene homopolymer. The chloroprene polymer (A) may be any modified chloroprene rubber, such as a sulfur-modified chloroprene rubber, a mercaptan-modified chloroprene rubber, a carboxyl-modified chloroprene rubber, a xanthogen-modified chloroprene rubber, or a mixture of one or more of these.

[0026] The z-average particle diameter of the chloroprene polymer (A) contained in the latex composition is preferably 100 nm or more, more preferably 250 nm or more. The z-average particle diameter of the chloroprene polymer (A) is preferably 500 nm or less, more preferably 450 nm or less. If the z-average particle diameter of the chloroprene polymer (A) is 100 nm or more and 500 nm or less, stable particles can be formed, which is preferable. The z-average particle diameter of the chloroprene polymer (A) can be obtained, for example, by measuring a sample prepared by diluting the chloroprene polymer latex or latex composition with pure water using a dynamic light scattering photometer.

[0027] <Production method of chloroprene polymer (A) and compounds used in the production> The polymerization method for producing the chloroprene polymer (A) is optional, but aqueous emulsion polymerization is preferred. The polymerization temperature for producing the chloroprene polymer (A) is preferably 30°C or higher, more preferably 33°C or higher, and particularly preferably 35°C or higher. The polymerization temperature for the chloroprene polymer (A) is preferably 55°C or lower, more preferably 50°C or lower, and particularly preferably 45°C or lower. A polymerization temperature of 30°C or higher is preferred because the productivity of the chloroprene polymer (A) is good and the adhesive strength of the resulting latex is within a desired range. A polymerization temperature of 55°C or lower is preferred because the vapor pressure of chloroprene is low, making the polymerization operation very easy and the mechanical properties of the resulting polymer, such as tensile strength, are good.

[0028] In producing the chloroprene polymer (A), in addition to the monomers used in the polymerization, an emulsifier, a polymerization initiator, a chain transfer agent, a polymerization terminator, etc. may be used.

[0029] An emulsifier may be added for emulsion polymerization. An anionic surfactant is preferable as the emulsifier. Examples of the anionic surfactant include rosin acid soap, sodium salt of naphthalenesulfonic acid condensate, sodium salt of dodecylbenzenesulfonic acid, and sodium salt of dodecylsulfuric acid. Since the use of rosin acid soap simplifies the solidification operation, it is preferable to use rosin acid soap as the emulsifier.

[0030] Hereinafter, the total amount of monomers used to form the chloroprene polymer (A) is taken as 100 parts by mass, and examples of the amount of the rosin acid soap used and the amount of the anionic surfactant other than the rosin acid soap used will be described. The amount of the rosin acid soap used is preferably 1.5 parts by mass or more, more preferably 1.6 parts by mass or more, and even more preferably 1.7 parts by mass or more, as converted to rosin acid. The amount of the rosin acid soap used is preferably 4.0 parts by mass or less, more preferably 3.7 parts by mass or less, and even more preferably 3.5 parts by mass or less, as converted to rosin acid. The amount of the anionic surfactant other than the rosin acid soap used is preferably 0.01 parts by mass or more, more preferably 0.02 parts by mass or more, and even more preferably 0.05 parts by mass or more. The amount of the anionic surfactant other than the rosin acid soap used is preferably 8.0 parts by mass or less, more preferably 7.0 parts by mass or less, and even more preferably 6.0 parts by mass or less. If the amount of emulsifier used is equal to or greater than the lower limit, poor emulsification is unlikely to occur, heat generation due to polymerization can be controlled, and problems such as the formation of aggregates and poor product appearance do not occur. Furthermore, if the amount of emulsifier used is equal to or less than the upper limit, the emulsifier does not remain in the chloroprene copolymer, so the chloroprene copolymer is unlikely to become sticky. As a result, if the amount of emulsifier used is equal to or less than the upper limit, problems with processability and operability due to adhesion to a mold (former) during molding of the chloroprene copolymer latex composition and adhesion during use of the molded product do not occur, and the color tone of the molded product does not deteriorate.

[0031] The particle size of the chloroprene polymer (A) can be adjusted by the amount of the anionic surfactant used. For example, the particle size of the chloroprene polymer (A) can be controlled by the amount of rosin acid and the amount of various emulsifiers relative to the mass parts of the monomer during polymerization. For example, the particle size of the chloroprene polymer (A) tends to be smaller as the amount of the emulsifier increases, and the particle size of the chloroprene polymer (A) tends to be larger as the amount of the emulsifier decreases.

[0032] The polymerization initiator can be selected from general radical polymerization initiators and is not particularly limited. For example, when the chloroprene polymer (A) is produced by emulsion polymerization, peroxides, azo compounds, etc. can be used as the polymerization initiator. The peroxide may be either an organic peroxide or an inorganic peroxide. Examples of peroxides that can be used include benzoyl peroxide, potassium persulfate, ammonium persulfate, etc. Examples of azo compounds that can be used include azobisisobutyronitrile, etc. A combination of two or more radical polymerization initiators can also be used as the polymerization initiator. The amount of the polymerization initiator used is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.2 parts by mass or more, based on 100 parts by mass of the monomer used in the polymerization. The amount of the polymerization initiator used is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less, based on 100 parts by mass of the monomer used in the polymerization.

[0033] In the polymerization, one or more kinds of co-catalysts may be used in combination with the polymerization initiator, such as anthraquinone sulfonate, potassium sulfite, and sodium sulfite.

[0034] The chain transfer agent can be selected from general chain transfer agents and is not particularly limited. Examples of the chain transfer agent include alkyl mercaptans such as n-dodecyl mercaptan. The amount of the chain transfer agent used is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, based on 100 parts by mass of the monomer used in the polymerization. The amount of the chain transfer agent used is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less, based on 100 parts by mass of the monomer used in the polymerization.

[0035] The polymerization terminator can be selected from general polymerization terminators and is not particularly limited. The polymerization terminator is added to the system when a predetermined polymerization conversion rate is reached. Examples of the polymerization terminator include phenothiazine, para-t-butylcatechol, hydroquinone, hydroquinone monomethyl ether, and diethylhydroxylamine. The amount of the polymerization terminator added can be any amount that can stop the polymerization reaction.

[0036] <pH and solid content of chloroprene polymer latex (A1)> The amount of chloroprene polymer (A) contained in a predetermined amount of chloroprene polymer latex (A1) can be determined, for example, from the amount of a dried product obtained when a predetermined amount of chloroprene polymer latex (A1) is dried at a predetermined temperature for a predetermined period of time. In this case, the amount of chloroprene polymer (A) is the mass of the dried product obtained by drying the chloroprene polymer latex (A1) minus the mass of substances other than the chloroprene polymer (A) that do not evaporate under the drying conditions for obtaining the dried product. In this embodiment, the drying conditions for obtaining the dried product are such that a predetermined amount of chloroprene polymer latex (A1) is left standing in an oven at 141°C for 30 minutes.

[0037] The proportion of the chloroprene polymer (A) in the chloroprene polymer latex (A1) is preferably 40% by mass or more, more preferably 45% by mass or more, and even more preferably 55% by mass or more. The proportion of the chloroprene polymer (A) in the chloroprene polymer latex (A1) is preferably 70% by mass or less, more preferably 65% ​​by mass or less, and even more preferably 62% by mass or less. When the proportion of the chloroprene polymer (A) in the chloroprene polymer latex (A1) is 40% by mass or more, the drying time can be reduced, and therefore the load on the drying device can be reduced. Furthermore, when the proportion of the chloroprene polymer (A) in the chloroprene polymer latex (A1) is 70% by mass or less, the fluidity of the chloroprene polymer latex (A1) can be set within a desired range.

[0038] The pH of the chloroprene polymer latex (A1) at 25° C. is preferably 11 or more, more preferably 11.5 or more, and further preferably 13 or more. The pH of the chloroprene polymer latex (A1) at 25° C. is preferably 14 or less.

[0039] The Brookfield viscosity of the chloroprene polymer latex is preferably 5.0 mPa·s or more, more preferably 10.0 mPa·s or more, and even more preferably 20.0 mPa·s or more. The Brookfield viscosity of the chloroprene polymer latex is preferably 500.0 mPa·s or less, more preferably 100.0 mPa·s or less, and even more preferably 50.0 mPa·s or less. If the Brookfield viscosity of the chloroprene polymer latex is 500.0 mPa·s or less, it is preferable because it has a desired viscosity and is easy to handle. If the Brookfield viscosity of the chloroprene polymer latex is 5.0 mPa·s or more, it is preferable because the diffusion speed of the blended additives (crosslinking agent, crosslinking accelerator, preservative, etc.) into the latex is fast and the maturation time is short. The Brookfield viscosity of the chloroprene polymer latex can be measured by the method adopted in the examples described later.

[0040] <Thiol compound (B)> The thiol compound (B) contained in the composition of this embodiment has two or more mercapto groups in one molecule. Although the description in this specification is not intended to be bound by a particular theory, it is presumed that the thiol compound (B) reacts with the double bond and the chloro group contained in the chloroprene polymer when heated to a temperature suitable for crosslinking treatment (crosslinking temperature) to form a crosslinked structure in the chloroprene polymer. In other words, when the thiol compound (B) is heated to the crosslinking temperature, it acts as a film-forming assistant that helps film formation when forming a molded body from the chloroprene polymer latex.

[0041] The thiol compound (B) is not particularly limited as long as it is a compound having two or more mercapto groups in one molecule. The number of mercapto groups in the thiol compound (B) is preferably 2 to 10, more preferably 2 to 8, and even more preferably 2 to 6 in one molecule. The molecular weight of the thiol compound (B) is preferably 3000 or less, more preferably 2500 or less, and even more preferably 2000 or less. The molecular weight of the thiol compound (B) is preferably 100 or more, more preferably 150 or more, and even more preferably 200 or more. The thiol compound (B) may be a reaction product of an aliphatic alcohol and a mercapto-substituted carboxylic acid, or may be a reaction product of a mercapto-substituted alcohol and a carboxylic acid. Here, the carboxylic acid may be either an aliphatic carboxylic acid or an aromatic carboxylic acid.

[0042] Examples of thiol compounds having two primary mercapto groups per molecule include butanediol bis(2-mercaptoacetate), hexanediol bis(2-mercaptoacetate), ethanediol bis(2-mercaptoacetate), 2,2'-(ethylenedithio)diethanethiol, ethylene glycol bis(3-mercapto-2-methylpropionate), propylene glycol bis(3-mercapto-2-methylpropionate), diethylene glycol bis(3-mercapto-2-methylpropionate), butanediol bis(3-mercapto-2-methylpropionate), octanediol bis(3-mercapto-2-methylpropionate), and bis(3-mercapto-2-methylpropyl)phthalate.

[0043] Examples of thiol compounds having two secondary mercapto groups in one molecule include 1,4-bis(3-mercaptobutyryloxy)butane, bis(1-mercaptoethyl)phthalate, bis(2-mercaptopropyl)phthalate, bis(3-mercaptobutyl)phthalate, ethylene glycol bis(3-mercaptobutyrate), propylene glycol bis(3-mercaptobutyrate), diethylene glycol bis(3-mercaptobutyrate), butanediol bis(3-mercaptobutyrate), octanediol bis(3-mercaptobutyrate), ethylene glycol bis(2-mercaptopropionate), propylene glycol bis(2-mercaptopropionate), diethylene glycol bis(2-mercapto propionate), butanediol bis(2-mercaptopropionate), octanediol bis(2-mercaptopropionate), ethylene glycol bis(4-mercaptovalerate), propylene glycol bis(4-mercaptoisovalerate), diethylene glycol bis(4-mercaptovalerate), butanediol bis(4-mercaptovalerate), octanediol bis(4-mercaptovalerate), ethylene glycol bis(3-mercaptovalerate), propylene glycol bis(3-mercaptovalerate), diethylene glycol bis(3-mercaptovalerate), butanediol bis(3-mercaptovalerate), octanediol bis(3-mercaptovalerate), and the like.

[0044] Examples of thiol compounds having two tertiary mercapto groups in one molecule include ethylene glycol bis(2-mercaptoisobutyrate), propylene glycol bis(2-mercaptoisobutyrate), diethylene glycol bis(2-mercaptoisobutyrate), butanediol bis(2-mercaptoisobutyrate), and octanediol bis(2-mercaptoisobutyrate).

[0045] Examples of thiol compounds having three primary mercapto groups in one molecule include trimethylolpropane tris(2-mercaptoacetate), trimethylolpropane tris(3-mercaptopropionate), and trimethylolpropane tris(3-mercapto-2-methylpropionate).

[0046] Examples of the thiol compound having three secondary mercapto groups in one molecule include trimethylolpropane tris(3-mercaptobutyrate), trimethylolpropane tris(2-mercaptopropionate), trimethylolpropane tris(4-mercaptovalerate), trimethylolpropane tris(3-mercaptovalerate), 1,3,5-tris(3-mercaptobutyloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and 1,3,5-tris(2-(3-sulfanylbutanoyloxy)ethyl)-1,3,5-triazinane-2,4,6-trione.

[0047] An example of a thiol compound having three tertiary mercapto groups in one molecule is trimethylolpropane tris(2-mercaptoisobutyrate).

[0048] Examples of the thiol compound having four primary mercapto groups in one molecule include pentaerythritol tetrakis(2-mercaptoacetate) and pentaerythritol tetrakis(3-mercaptopropionate).

[0049] Examples of thiol compounds having four secondary mercapto groups per molecule include pentaerythritol tetrakis(3-mercaptobutyrate), pentaerythritol tetrakis(2-mercaptopropionate), pentaerythritol tetrakis(3-mercapto-2-propionate), pentaerythritol tetrakis(4-mercaptovalerate), pentaerythritol tetrakis(3-mercaptovalerate), and the like.

[0050] An example of a thiol compound having four tertiary mercapto groups in one molecule is pentaerythritol tetrakis(2-mercaptoisobutyrate).

[0051] An example of a thiol compound having six primary mercapto groups in one molecule is dipentaerythritol hexakis(3-mercapto-2-methylpropionate).

[0052] Examples of thiol compounds having six secondary mercapto groups per molecule include dipentaerythritol hexakis(3-mercaptobutyrate), dipentaerythritol hexakis(2-mercaptopropionate), dipentaerythritol hexakis(4-mercaptovalerate), dipentaerythritol hexakis(3-mercaptovalerate), and the like.

[0053] An example of a thiol compound having six tertiary mercapto groups in one molecule is dipentaerythritol hexakis(2-mercaptoisobutyrate).

[0054] The mercapto group contained in the thiol compound (B) may be any of a primary mercapto group, a secondary mercapto group, and a tertiary mercapto group, but is preferably a primary mercapto group or a secondary mercapto group, and more preferably a secondary mercapto group. In the case of a primary mercapto group or a secondary mercapto group, the steric hindrance is smaller than that of a tertiary mercapto group, so it is considered that the reactivity is better than that of a tertiary mercapto group. The multiple mercapto groups possessed by the thiol compound (B) may be mercapto groups of the same series, or may be mercapto groups of different series. For example, the thiol compound (B) may have a primary mercapto group and a secondary mercapto group.

[0055] The mercapto group may be contained as any partial structure in the molecule, but is preferably contained in the molecule as a partial structure represented by CH3(SH)CHCH2COOCH2-. Examples of suitable thiols having a partial structure represented by CH3(SH)CHCH2COOCH2- include 1,4-bis(3-mercaptobutyryloxy)butane (a specific example of the product is KarenzMT (registered trademark) BD1 manufactured by Showa Denko K.K.), 1,3,5-tris(2-(3-sulfanylbutanoyloxy)ethyl)-1,3,5-triazinane-2,4,6-trione (a specific example of the product is KarenzMT (registered trademark) NR1 manufactured by Showa Denko K.K.), pentaerythritol tetrakis(3-mercaptobutyrate) (a specific example of the product is KarenzMT (registered trademark) PE1 manufactured by Showa Denko K.K.), and trimethylolpropane tris(3-mercaptobutyrate) (a specific example of the product is KarenzMT (registered trademark) TPMB manufactured by Showa Denko K.K.).

[0056] When the above-mentioned thiol compound (B) is used to prepare the composition of this embodiment, a molded article having performance equal to or higher than that of a thiourea-based compound can be produced without using a thiourea-based compound such as ethylenethiourea and 1,3-diphenylthiourea. Here, ethylenethiourea is included in the list of substances of very high concern in the REACH (Registration, Evaluation, Authorization and Restriction of CHemicals) regulation because it exhibits reproductive toxicity. 1,3-diphenylthiourea is also a thiourea-based compound like ethylenethiourea, so it has a high environmental load and it is desirable to refrain from using it. Therefore, the composition of this embodiment has the advantage that a molded article having performance equal to or higher than that of a thiourea-based compound can be produced without using a thiourea-based compound having a high environmental load.

[0057] The amount of the thiol compound (B) in the composition is preferably 0.05 parts by mass or more, more preferably 0.25 parts by mass or more, and even more preferably 2 parts by mass or more, relative to 100 parts by mass of the chloroprene polymer (A). When the amount of the thiol compound (B) in the composition is equal to or more than the above-mentioned lower limit, a crosslinked structure is obtained in the molded body by the crosslinking treatment, and the elasticity of the molded body is increased and the breaking strength of the molded body is increased, which is preferable. The amount of the thiol compound (B) in the composition is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 11 parts by mass or less, relative to 100 parts by mass of the chloroprene polymer (A). When the amount of the thiol compound (B) in the composition is equal to or less than the above-mentioned upper limit, the dispersion of the thiol compound (B) in the chloroprene polymer (A) is good, so that the crosslinked structure is easily formed uniformly in the molded body, and the decrease in the breaking strength of the molded body and the decrease in the breaking elongation of the molded body can be prevented, which is preferable.

[0058] Other components that may be included in the composition The composition of the present embodiment may further include one or more of a metal oxide and a crosslinking accelerator (vulcanization accelerator) for a crosslinking treatment.

[0059] The metal oxide can be used to promote crosslinking of the chloroprene polymer (A) and can act as one or more of a crosslinking agent, a crosslinking promoter, and a crosslinking assistant. For example, zinc oxide can be used as the metal oxide. In addition to zinc oxide, the metal oxide can be, for example, lead oxide, lead tetroxide, etc., but zinc oxide is preferred in consideration of the burden on the environment. The metal oxide can be magnesium oxide, calcium oxide, etc.

[0060] The amount of the metal oxide in the composition of this embodiment is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, based on 100 parts by mass of the chloroprene polymer (A). The amount of the metal oxide in the composition is preferably 15 parts by mass or less, more preferably 12 parts by mass or less, and even more preferably 10 parts by mass or less, based on 100 parts by mass of the chloroprene polymer (A). In this case, an appropriate crosslinking rate is obtained, insufficient crosslinking is unlikely to occur, and scorching is unlikely to occur.

[0061] The crosslinking accelerator (vulcanization accelerator) may be selected from crosslinking accelerators generally used for crosslinking chloroprene polymers, such as dithiocarbamate crosslinking accelerators, thiazole crosslinking accelerators, thiuram crosslinking accelerators, guanidine crosslinking accelerators, and xanthogenate crosslinking accelerators. Examples of dithiocarbamate crosslinking accelerators include sodium dibutylthiodicarbamate, zinc dibutylthiodicarbamate, and zinc diethylthiodicarbamate. Examples of thiazole crosslinking accelerators include di-2-benzothiazolyl disulfide. Examples of thiuram crosslinking accelerators include tetraethylthiuram disulfide and tetrabutylthiuram disulfide. Examples of guanidine crosslinking accelerators include diphenylguanidine and di-orthotoluylguanidine. From the viewpoint of environmental load, it is preferable that the composition of the present embodiment does not contain a crosslinking accelerator.

[0062] The composition of the present embodiment may further contain other additives. Examples of additives that may be contained include a pH adjuster, a pigment, a colorant, and an antioxidant. An example of an antioxidant is an oligomeric hindered phenol. The oligomeric hindered phenol is a butylated reaction product of dicyclopentadiene and p-cresol.

[0063] [Molded body] A molded article can be formed by subjecting the composition of the present embodiment to a crosslinking treatment. Examples of the molded article include gloves, balloons, rubber threads, boots, etc. The type of gloves obtained by the crosslinking treatment of the composition is arbitrary, and may be, for example, one or more of household gloves, industrial gloves, examination gloves, medical examination gloves, and surgical gloves.

[0064] The molded article is formed, for example, by drying the composition of this embodiment and then raising the temperature to a crosslinking temperature. For example, in the immersion processing method, a mold is immersed in the composition of this embodiment, and a mixture of the chloroprene polymer (A) and the thiol compound (B) is solidified on the surface of the mold, followed by drying and crosslinking to obtain a film-like molded article. The drying process may include rough drying at a relatively low temperature before the crosslinking process, for example, to avoid blisters, pinholes, and the like.

[0065] In the crosslinking treatment, the mixture of the chloroprene polymer (A) and the thiol compound (B) after the drying treatment is heated to a desired crosslinking temperature for a desired crosslinking time. The crosslinking temperature of the chloroprene polymer is preferably 110°C or higher, more preferably 115°C or higher, and even more preferably 120°C or higher. The crosslinking temperature of the chloroprene polymer is preferably 160°C or lower, more preferably 150°C or lower, and even more preferably 140°C or lower. The crosslinking time of the chloroprene polymer is preferably 10 minutes or higher, more preferably 20 minutes or higher. The crosslinking time of the chloroprene polymer can be 60 minutes or less, and more preferably 30 minutes or less. EXAMPLES

[0066] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples. In the following description of the examples, "parts" refers to "parts by mass" unless otherwise specified. First, the measurement methods and calculation methods of physical properties used in the examples and comparative examples will be described, and then each example will be described.

[0067] [Methods for measuring physical properties of chloroprene polymer latex (A1) and molded product] <Polymerization Conversion Rate of Chloroprene Polymer (A)> The emulsion after the start of polymerization of the chloroprene polymer (A) was collected and dried by standing in an oven at 141°C for 30 minutes to obtain a dry product. The dry product obtained by the drying process contains polymer and solids other than the polymer. Therefore, the mass of the solids other than the polymer was calculated from the amount of the polymerization raw materials charged, and the mass of the dry product obtained by drying the emulsion after polymerization minus the mass of the solids other than the polymer was determined as the "amount of polymer produced," and the polymerization conversion was calculated by formula (1). Polymerization conversion rate [mass%] = [(amount of polymer produced / total amount of monomer charged)] × 100 (1) The "total monomer charge mass" in formula (1) is the sum of the charge amount of chloroprene contained in the amount of emulsion collected to obtain a dry product and the charge amount of comonomer.

[0068] <Solid content of chloroprene polymer latex (A1)> A predetermined amount of chloroprene polymer latex (A1) was collected, and the mass of the collected chloroprene copolymer latex (A1) was weighed. The weighed chloroprene copolymer latex (A1) was then left to stand in an oven at 141°C for 30 minutes to dry and obtain a dry solid. The solid content was calculated according to formula (2) from the mass of the latex before drying and the mass of the solid content obtained after drying. Solid content (mass%) = [(mass of solids after drying) / (mass of latex before drying)]×100 (2)

[0069] <z-average particle size of chloroprene polymer (A)> The chloroprene polymer latex (A1) was diluted with pure water until the ratio of the chloroprene polymer (A) was 0.01 to 0.1 mass% or less to prepare a measurement sample. The measurement sample thus obtained was measured with a dynamic light scattering photometer (ZETASIZER (registered trademark) Nano-S manufactured by Malvern Panalytical Ltd) to determine the z-average particle size of the chloroprene polymer (A) in the chloroprene polymer latex (A1).

[0070] <Viscosity> The chloroprene polymer latex (A1) to be used as the test specimen was placed in a 300 mL polypropylene beaker, and the inside of the beaker was made completely free of air bubbles. Using a B-type viscometer as specified in JIS K7117-1:1999, the viscosity of the second measurement, in which the measured value was within 5% of the measured value in successive measurements, was recorded as the viscosity. Equipment: BROOKFIELD Viscometer DV-E LVDVE115, Spindle: No.1 spindle, Rotation speed: 60 rpm, Temperature: 25℃.

[0071] <Evaluation of physical properties of molded products obtained by crosslinking treatment> According to JIS-K6251-2017, the crosslinked film was cut into a No. 6 dumbbell to obtain a test piece. The film test piece was subjected to a tensile test according to JIS-K6251-2017 to obtain the modulus at 100% elongation (M100), tensile strength (T B ), and elongation at break (E B ) was measured.

[0072] [Production Example of Chloroprene Polymer Latex (A1-1)] Into a 5-L reactor, 2.0 kg of 2-chloro-1,3-butadiene (manufactured by Tokyo Chemical Industry Co., Ltd.), 1.04 kg of pure water, 40 g of rosin acid (manufactured by Arakawa Chemical Industries, Ltd., R-300), 2 g of n-dodecyl mercaptan (manufactured by Tokyo Chemical Industry Co., Ltd.), 100 g of a 20 mass% aqueous potassium hydroxide solution (special grade product manufactured by Wako Pure Chemical Industries, Ltd.), 12.8 g of a sodium salt of a β-naphthalenesulfonic acid formalin condensate (manufactured by Kao Corporation), and 6.7 g of a 15 mass% aqueous solution of sodium dodecylbenzenesulfonate (manufactured by Kao Corporation, Neopelex (registered trademark) G-15). The amounts of each substance charged are 52 parts of pure water, 2 parts of rosin acid, 0.1 part of n-dodecyl mercaptan, 1 part of potassium hydroxide, 0.64 parts of sodium salt of β-naphthalenesulfonic acid formalin condensate, and 0.05 parts of sodium dodecylbenzenesulfonate, relative to 100 parts of 2-chloro-1,3-butadiene. The starting materials charged in the reactor were emulsified, and the rosin acid was converted into rosin soap. Then, using 0.3 parts of potassium persulfate (a first-class product manufactured by Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, polymerization was carried out at a temperature of 40°C for 5 hours under a nitrogen gas atmosphere. The polymerization was stopped when it was confirmed that the polymerization conversion rate was 94% by mass or more. The polymerization conversion rate was calculated according to formula (1). The unreacted monomer was removed by steam distillation to obtain a chloroprene polymer latex (A1-1). The solid content in the chloroprene polymer latex (A1-1) was 58 mass%. The solid content was calculated using formula (2). The pH of the chloroprene polymer latex (A1-1) was 13.0. Furthermore, the z-average particle size of the chloroprene polymer contained in the chloroprene polymer latex (A1-1) obtained in the production example was 20 μm. The viscosity of the chloroprene polymer latex (A1-1) obtained in the production example was 40 mPa s.

[0073] [Example 1] 100 parts of chloroprene polymer latex (A1-1) (about 58 parts of chloroprene polymer), 5 parts of zinc oxide (AZ-SW, manufactured by Osaki Kogyo Co., Ltd.), 2 parts of zinc dibutyldithiocarbamate (II) (Noccela (registered trademark) BZ, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), 1 part of oligomer-type hindered phenol antioxidant (Cellosol (registered trademark) K-840, manufactured by Chukyo Yushi Co., Ltd.), and 3 parts of 1,4-bis(3-mercaptobutyryloxy)butane (Karens MT (registered trademark) BD1, manufactured by Showa Denko K.K.) were charged into a stirring tank equipped with a three-one motor. The amount of each substance left to stand in the stirring tank is shown in the column of Example 1 in Table 1. The contents of the stirring tank were stirred for 5 minutes at 300 rpm by the three-one motor to obtain a chloroprene polymer latex composition. Thereafter, the chloroprene polymer latex composition was left to stand at room temperature (20°C) for 24 hours to be aged.

[0074] [Examples 2 to 11, Comparative Examples 1 and 2] Chloroprene polymer latex compositions were prepared in the same manner as in Example 1, except that the compositions of the substances used in the preparation were as shown in Table 1. In Comparative Examples 1 and 2, 1,3-diphenyl-2-thiourea was used instead of the thiol compound (B).

[0075] [Table 1]

[0076] [evaluation] <Formation of Molded Product> A ceramic plate measuring 200 mm in length, 100 mm in width, and 5 mm in thickness was used as the immersion film mold. In order to adhere calcium nitrate, which serves as a coagulant, to the surface of the immersion film mold, the immersion film mold was immersed in a coagulation liquid containing 30% by mass calcium nitrate aqueous solution / methanol / clay in a ratio of 90:10:5 (by mass). The clay used here was aluminum silicate (Crown Clay, manufactured by Southern Clay Co., Ltd.). The immersion film mold was removed from the coagulation liquid and then dried in an oven at 40°C for 5 minutes.

[0077] The dried mold was immersed in the chloroprene polymer latex composition obtained in Example 1, and the solid content of the chloroprene polymer latex composition was deposited on the surface of the mold. After immersion for a predetermined period of time, the mold was taken out and placed in an oven at 70° C. for drying for 30 minutes. After drying, the mold with the solid matter deposited on the surface was placed in an oven and crosslinked at a crosslinking temperature of 130°C. The crosslinking time was set to three times: 10 minutes, 20 minutes, and 30 minutes. After the crosslinking, the mold with the film formed on the surface by the crosslinking was allowed to cool in the air. After cooling, the film was cut out from the surface of the mold to obtain a film as a molded product after the crosslinking.

[0078] For each of the compositions prepared in Examples 2 to 11 and Comparative Examples 1 and 2, a molded article was formed in the same manner as for the composition prepared in Example 1. The films obtained using the compositions prepared in Examples 1 to 11 and Comparative Examples 1 and 2 all had a thickness of about 0.15 to 0.25 mm.

[0079] The crosslinked films formed using the compositions prepared in Examples 1 to 11 and Comparative Examples 1 and 2 were subjected to a 100% elongation modulus (M100) tensile strength (T B ), and elongation at break (E B The results are shown in Table 2.

[0080] [Table 2]

[0081] No significant difference was observed in the physical properties of the molded articles formed from the compositions obtained in each of Examples 1 to 4 and Comparative Example 1. From this, it can be said that in a system containing zinc dibutyldithiocarbamate, when a thiol compound (B) is used, a film having physical properties equivalent to or superior to those in the case of using a crosslinking accelerator (such as 1,3-diphenyl-2-thiourea) that has a relatively high environmental load can be formed.

[0082] No significant difference was observed in the physical properties of the molded articles formed from the compositions obtained in each of Examples 5 to 11 and Comparative Example 2. Therefore, even in a system not containing zinc dibutyldithiocarbamate, it can be said that by using the thiol compound (B) instead of a crosslinking accelerator (such as 1,3-diphenyl-2-thiourea) that has a relatively high environmental load, a film having physical properties equivalent to or greater than those in the case of using a crosslinking accelerator that has a relatively high environmental load can be formed.

Claims

1. The present invention comprises a chloroprene polymer (A) and a thiol compound (B) having two or more mercapto groups in one molecule, The thiol compound (B) has two or more partial structures represented by CH 3 (SH)CHCH 2 COOCH 2 - in one molecule, The latex composition has a content of the thiol compound (B) of 0.05 to 20 parts by mass relative to 100 parts by mass of the chloroprene polymer (A).

2. 2. The latex composition according to claim 1, wherein the chloroprene polymer (A) is at least one selected from the group consisting of a homopolymer of chloroprene and a copolymer of chloroprene and another monomer copolymerizable with the chloroprene.

3. 3. The latex composition according to claim 2, wherein the ratio of the other monomer in the monomers used to form the chloroprene polymer (A) is 30 mass % or less.

4. The latex composition according to any one of claims 1 to 3, wherein the thiol compound (B) has 2 to 10 mercapto groups in one molecule.

5. The latex composition according to any one of claims 1 to 4, wherein the thiol compound (B) is at least one selected from the group consisting of 1,4-bis(3-mercaptobutyryloxy)butane, 1,3,5-tris(2-(3-sulfanylbutanoyloxy)ethyl)-1,3,5-triazinane-2,4,6-trione, pentaerythritol tetrakis(3-mercaptobutyrate), and trimethylolpropane tris(3-mercaptobutyrate).

6. The latex composition of any one of claims 1 to 5, further comprising a metal oxide.

7. 7. The latex composition of claim 6, wherein said metal oxide is zinc oxide.

8. A molded article formed by using the latex composition according to any one of claims 1 to 7.

9. A method for producing a molded article, comprising heating the latex composition according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • PVC (Polyvinyl Chloride) / CR (Chloroprene Rubber) composite glove and making process thereof

    CN104151747A

  • Tire rubber

    CN104804245A

  • Chloropren rubber composition

    JP2002138165A

  • Chloroprene polymer composition, and method for producing the same

    JP2013177504A

  • Chloroprene polymer latex and manufacturing method therefor

    JP2019143002A